Effects of Bilateral Superior Oblique "Hang-Back" Recession in Treatment of A-pattern Strabismus with Superior Oblique Overaction. (2nd January 2016) - Li, Yueping; Ma, Huizhi; Zhao, Kanxing
ABSTRACT: Purpose : To investigate the efficacy and safety of bilateral hang-back recession of superior oblique (SO) muscles in the treatment of A-pattern strabismus with superior oblique overaction (SOOA). Methods : Thirty-one (31) patients (62 eyes) with A-pattern horizontal deviation and SOOA underwent hang-back recession of SO and retrospective analysis of the surgical amount of hang-back recession of SO, preoperative and postoperative A-pattern, ocular motility, and corrected objective torsion. Patients were evaluated before and 6 to 9 months after surgery. Results : The average A-pattern horizontal deviation was 27.58 ±11.47 prism diopters (PD) before surgery and 3.48 ± 3.70 PD after surgery (n=31, P <0.05). The mean corrected A-pattern was horizontal deviation 24.10 ± 10.32 PD. The average scale of SOOA on a scale of +1 to +4 was +3.05 ± 0.80 before surgery and +0.42 ± 0.50 after surgery in 62 eyes ( P <0.05). The mean corrected objective torsion was 4.91°± 4.53°. The surgical amount of SO hang-back recession ranged from 4 to 10 mm (mean: 7.62 ± 1.18 mm), which was related to the preoperative A-pattern and corrected A-pattern. There were no surgical complications. Conclusions : SO hang-back recession is a safe and efficient option for A-pattern caused by SOOA.